(untitled) (AYUSHDHARA, 2017)
Madatyaya (Alcohol Withdrawal Syndrome) is a crucial problem in India, many people lose their life due to it. Madya (Alcohol) is when taken judiciously act like Nector but when used without restriction act like poison and creates symptoms of Madatyaya (Alcohol withdrawal Syndrome). It ruins our social mental and economic status. As a doctor it is our responsibility to help such alcohol addicts by counselling and treating them to recover from this addiction. It was with this intention that the disease Madatyaya has been chosen for the study. A study was conducted to access efficacy of ‘‘Mrudvikadi Kashayam & Kalyanaka Ghrita Nasyam’’. 50 patients of Madatyaya were selected in control group and 50 patients in trial group by random selection method. Control group was not given any medicine; however they were observed for 42 days for all parameters. Trial group patients received medications in the form of Gandharva Haritaki for the first 6 days followed by ‘Mrudvikadi Kashayam panartha’ in the dose of 80ml with Jala (water) in 2 divided dose, morning and evening after food for the duration of 42 days and Kalayanakaa ghrita Pratimarsha Nasya 6 drops in each nostril from day 7 for 42 days. Gradation scale was used for the purpose of case taking; however at the time of statistical analysis Wileoxan test, Mann-Whitney test, Paired t-test, Unpaired t-test were used. It revealed that ‘Mrudvikadi Kashayam & Kalyanaka Ghrita Nasya’ is effective in Madatyaya. It significantly reduces the symptoms. Agnimandya, Aruchi, Hrullas, Chardi, Daha, Murcha, Gaurav, Kasa, Tandra, Atisweda, Daurbalya and Nidranasha. Both the groups showed better efficacy in alleviation of symptoms of Pralap, Parshwashoola, Trishna and Shirokampa. ‘Mrudvikadi Kashayam’ is Balya, Rasayana agni deepana and srotoshodhaka and Pachana, and the utility of Kalyanaka ghrita indicates its action on Manovahastrotas by empowering it. ‘Mrudvikadi Kashayam’ enhances the nutritional status of such alcoholic patients, also appetite and metabolism is increased due to its Deepan karma, which directly affects the Hb level in patients. As Pippali, Yashtimadhu, possesses Vishghna property, ‘Mrudvikadi Kashayam’ de-toxified the toxic effects of Madya on Liver thus helpful in lowering LFT values. In Madatyaya due to Madya along with Agni dhushti, Srotodushti is also a pathological change. Hence, to treat that Mrudweekadi Kashaya and Kalyanaka Ghrita was selected.